Avaliação pós-ocupação em conjunto habitacional de interesse social construído com paredes de concreto moldadas in loco na cidade de Santa Maria, RS - Oliveira, Daiana Fauro de (2016)
Post-occupancy evaluation is a mechanism of great importance for the performance evaluation of a building, as it makes it possible to evaluate the quality of the built environment regarding technical, functional, aesthetic and behavioral factors and diagnosing negative aspects and deficiencies in the space.Therefore, this work evaluated the social interest housing complex Loteamento Zilda Arns , in Santa Maria-RS, using methods such as questionnaires applied to residents, technical inspections and photographic surveys, the goal being to identify deficiencies and pathological manifestations of the construction process with cast-in-place concrete walls as well as to evaluate the quality and performance of the material and finishes used in the housing units and the complex itself. The opinion and satisfaction of the residents were taken into account. Sixty randomly selected housing units from the complex were inspected. These buildings are built with cast-in-place concrete walls, a commonly used rapid implementation system for massive building of housing.The main problem identified in the housing complex is related to the absence of collective equipment and leisure areas. As far as housing is concerned, pathological manifestations were identified with regards to the construction process and quality of the material applied in the buildings. Despite the problems uncovered by the postoccupancy evaluation, most of the residents are satisfied, which might not be related to the constructive quality and environmental comfort levels offered by their current housing unit but rather to the precarious state of their previous homes.